The Rorschach in the 21st century: The assessment of mental representation - Blatt, Sydney J. (2003)
The Rorschach test has considerable potential to contribute to the study of cognitive processes, especially the representational world and of how individuals construct meaning. The representation of self and other is currently a major topic in attachment research and in social cognition and is very relevant for clinical psychology and psychiatry because it provides a way of understanding psychopathology that goes beyond the simple listing of manifest symptoms that is so prevalent today in descriptive psychiatry. This new emphasis on mental representation should enable us to extend our understanding of psychopathology and to discover new ways of systematically assessing a wide range of psychological disturbances.